2015
DOI: 10.1681/asn.2014040396
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Validity of Surrogate Outcomes for ESRD

Abstract: Validation of current and promising surrogate outcomes for ESRD in randomized controlled trials (RCTs) has been limited. We conducted a systematic review and meta-analysis of RCTs to further inform the ability of surrogate outcomes for ESRD to predict the efficacy of various interventions on ESRD. MEDLINE, EMBASE, and CENTRAL (from inception through September 2013) were searched. All RCTs in adults with proteinuria, diabetes, or CKD stages 1-4 or renal transplant recipients reporting $10 ESRD events and a surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 58 publications
0
28
1
1
Order By: Relevance
“…Existing literature supports that the hemodynamic effects of RAS blockade may contribute to up to 30% acute, reversible reduction in eGFR [58,59]. Nonetheless, in our study, the outcome of 50% reduction in eGFR across two consecutive values or ESRD suggests that RAS blockade does not protect against chronic adverse renal outcomes in obese, non-diabetic patients compared to other antihypertensive agents [60]. Additionally, our study corroborates existing data that RAS blockade is protective against the development of diabetes, but not mortality in this patient population [52].…”
Section: Discussioncontrasting
confidence: 51%
“…Existing literature supports that the hemodynamic effects of RAS blockade may contribute to up to 30% acute, reversible reduction in eGFR [58,59]. Nonetheless, in our study, the outcome of 50% reduction in eGFR across two consecutive values or ESRD suggests that RAS blockade does not protect against chronic adverse renal outcomes in obese, non-diabetic patients compared to other antihypertensive agents [60]. Additionally, our study corroborates existing data that RAS blockade is protective against the development of diabetes, but not mortality in this patient population [52].…”
Section: Discussioncontrasting
confidence: 51%
“…5 As noted by the FDA, these methods of biomarker use are not mutually exclusive; for example, in diabetic kidney disease trials, urine albumin is used as a prognostic biomarker to preferentially enroll patients at higher risk of reaching the trial’s end point, and as a pharmacodynamic biomarker to support proof-of-concept studies and aid in dose selection. 7 Novel biomarkers used in isolation may not perform as well as a composite biomarker score in combination with existing clinical information and traditional tests. 8,9 …”
Section: Kidney Injury Biomarkers: Value In Drug Developmentmentioning
confidence: 99%
“…As evidence of this CQ, albuminuria/proteinuria at baseline and at the end of the study was measured, and six RCT articles [42][43][44][51][52][53] and four meta-analysis articles [45,46,54,55] using ESRD as the endpoint were adopted.…”
Section: Discussionmentioning
confidence: 99%
“…These randomized controlled trials and post hoc analysis results confirmed a relationship between the decrease in albuminuria/proteinuria as a result of treatment using RA inhibitors for diabetic nephropathy and prevention of progression to ESRD. On the other hand, there are four papers reporting systematic review/ meta-analysis reviewing the usefulness of decrease in albuminuria/proteinuria as a surrogate endpoint [45,46,54,55]. In a meta-analysis of 32 randomized controlled trials (9008 subjects) evaluating five treatment interventions (RA inhibitor, Ca antagonist, intensive depressor therapy, low protein diet, and immunosuppressive drug) with renal disease progression as an outcome, the relationships between changes in albuminuria 2.5-13 months later and composite endpoints (doubling of serum creatinine level, ESRD, death) were investigated [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation